New trends in economic integration : the emergence of regional multinationals and intra-regional flows/ Trevor Farrell - Farrell, Trevor M. A. (Kingston, Jamaica: Ian Randle Publishers, 2003)
Discusses the regionalisation of CARICOM enterprises and the emergence of Caribbean multinationals. Deals with the intra-regional delivery and sale of services as well as the growth of intra-regional portfolio investment.
A publication of the UWI CARICOM Project
Keywords: Caribbean Community Secretariat